Evaluasi Layanan Penyampaian Keluhan Masyarakat Berbasis Teknologi Informasi pada Pemerintah Kabupaten Sidoarjo Menggunakan Framework COBIT 5 - Fajri Ilhamdi; Widhy Hayuhardhika Nugraha Putra; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Sidoarjo Regency Government has implemented a website-based service for public complaint called Pusat Pelayanan Pengaduan Masyarakat (P3M). However, in the process of implementing there is a problem is the user requirements that are not right. So that the service is less attractive to the public as a user. In fact, people prefer to complain through the Sidoarjo Regency Government social media such as Facebook. Therefore, the evaluation was carried out using the Framework Object Control for Information and Related Technologies (COBIT) 5. The process used is Manage Requirements Definition (BAI02) and Manage Solutions Identification and Build (BAI03). This process is chosen because both have activities that support requirements governance. Retrieval of data in this study was carried out by questionnaires, interviews and document study. Respondents were selected using the RACI Chart calculation for each process. On the questionnaire sheet contains questions related to governance requirements on P3M services. Then the interview aims to ask for targeted levels of P3M services. After data processing, capability level in the BAI02 and BAI03 processes at level 0 (incomplete process). Then the targeted level of the two processes at level 2 (managed process), therefore there is a gap of 2 (two). Then the researcher compiled a recommendation document that would complement each activity in the BAI02 and BAI03 processes. Each recommendation will be explained clearly in order to achieve capability level 2 (managed process).